KAJIAN PERENCANAAN SALURAN TERSIER DAN KUARTER PADA DAERAH IRIGASI RANAH SINGKUANG KECAMATAN KAMPAR KABUPATEN KAMPAR - Sutopo - (Jurnal APTEK, 2012)
The aim of this research is planning secondary and tertiary canalin Ranah Singkuang Irrigation Area ofKampar District through variation of crop patterns. Ranah Singkuang Irrigation area functional is 241.5 Ha.The processing of agricultural land at the location is also done twice a year with padi-padi-bero crop pattern.This research method used of criteria design irrigation at published Public Works Republic of Indonesia to obtain secondary and tertiary canal dimension in Ranah Singkuang Irrigation Area, District Kampar for net field requirement.The results of four early planting alternative planned. Crop pattern is obtained which get the greatest discharge 1,381 lt/s/ha is padi-padi-bero at early planting January period I. Result of analysis for secondary and tertiary trapezium canal dimension respectively for width of canal (b) 0.42 m and 0.2 m, water level of canal (h) 0.42 m and 0.2 m , working of canal (w) 0.14 m dan 0.67 and sloope of canal (I) 1.8 x 10-4 and 1.8 x 10-4 .